Tennyson's language - Hair, Donald S. (Toronto : University of Toronto Press, 1991)
Hair offers a significant contribution to the development of linguistic theory in Britain while also providing some close readings of key passages of Tennyson's work and examinations of the poet's faith and views of society.
Introduction -- 'Matter-moulded forms of speech' -- 'A landscape-painter in words, a colourist' -- 'I hear a voice' -- 'At the sound of my name' -- 'Heart-affluence in discursive talk': in memoriam -- 'Man's word is god in man': Idylls of the king -- Conclusion.
Online resource; title from PDF title page (EBSCO, viewed April 8, 2016).
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Language; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Knowledge -- Language and languages; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Langage; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Et le langage et les langues; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892; Tennyson, Alfred, -- (1809-1892) -- Langue; Tennyson, Alfred; Language and languages -- Philosophy -- History -- 19th century; Langage et langues -- Philosophie -- Histoire -- 19e siècle.; POETRY -- English, Irish, Scottish, Welsh; Language and languages; Language and languages -- Philosophy; Sprache; Philosophie du langage -- Histoire; 1800-1899; English poetry; History